Axiological Associations of the Notion of Sustainable Development - Piotrowski, Rober (Problemy Ekorozwoju, 2007)
Basic axiological associations of the notion of sustainable development are analysed from two perspectives: anthropocentric and ecocentric. Some difficulties in establishing and implementing fully-fledged environmental ethics are also emphasised.